Moral Development in Religious Education : Insights from Comparative Studies - Paulo Freire; Moacir Gadotti; Jose Carlos Libaneo (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
This article explores the role of religious education in shaping students' moral development through a comparative analysis of different educational systems. By examining the curricula and pedagogical approaches in various cultural and religious contexts, the study identifies commonalities and differences in how moral values are taught. The findings highlight the importance of integrating universal ethical principles alongside religious teachings to nurture well-rounded individuals.